Influence of abaca fiber and hydrated lime for the improvement of hot mix asphalt, Trujillo, Peru, 2023 - Coronel Saavedra, Risto Yansey; Garcia Garcia, Anderson Bryan; Martell Ortiz, Juan Carlos; Noriega Vidal, Eduardo Manuel; Henríquez Ulloa, Juan Paul Edward; Valdivieso Velarde, Alan Yordan; Rodríguez Beltrán, Eduar Jose (LACCEI, 2024)
The general objective of the current research work was to determine the influence of abaca fiber and hydrated lime for the improvement of hot mix asphalt, Trujillo, Peru, 2023. It was carried out through an experimental design - quasi-experimental, type applied, with a quantitative approach and an explanatory level. The population was represented by all hot asphalt briquettes and the sample consisted of 33 briquettes with the addition of abaca fiber and hydrated lime at 0.0%, 1.0%, 1.5% and 2.0%. Non-Probabilistic, intentional sampling was used. Direct experimental observation was applied as a technique and the observation guide and results collection sheet were used as instruments. The results indicated that by adding 1.5% abaca fiber and 2.0% hydrated lime, improvements were obtained in the asphalt mixture with stability values ​​of 1001kg and 1281kg, creep values ​​of 2.62 and 3.73 and a void content of 4.12% and 4.21%, respectively. In conclusion, 1.5% abaca fiber and 2.0% hydrated lime positively influence the improvement of hot mix asphalt, Trujillo, Peru, 2023